A rare case report on infratemporal, masticator and parapharyngeal space infection secondary to decayed upper wisdom tooth - Rajanikanth B.R.; Prasad K.; Achar A.T. (Journal of Oral Medicine and Oral Surgery)
Introduction: Space infections of infratemporal and temporal spaces are rare. These spaces rarely present as the primary space. An infection here could migrate to cavernous sinus through the pterygoid plexus or into the orbit through the valveless ophthalmic veins which has dangerous consequences. Case report: A 66-year-old male reported to the Department of oral and maxillofacial surgery with difficulty in mouth opening and pain in left temporal region. Patient was prescribed antibiotics and analgesics and recalled for extraction of upper left third molar under local anaesthesia once mouth opening improved. After 15 days, patient presented with generalized edema in relation to left side of the face. MRI revealed abscess in Left infratemporal spaces and edema of the left parotid, pharyngeal space and effusion of left temporomandibular joint. Incision and drainage along with extraction of upper left third molar was performed under general anaesthesia. Conclusion: Infratemporal space is a primary space involved in odontogenic infections and symptoms of this are hard to identify. If left untreated, it may spread to deeper spaces. Immediate intervention in the form of extraction of offending teeth and/or incision and drainage along with adequate intravenous antibiotics and analgesics will help the clinician to treat this condition.